Use of force in international law : a case-based approach - Ruys, Tom; Corten, Olivier; Hofer, Alexandra, 1990- (Oxford, United Kingdom : Oxford University Press, 2018)
Since the adoption of the UN Charter in 1945, the use of cross-border force has been frequent. This volume invites a range of experts to examine over sixty conflicts, from military interventions to targeted killings and hostage rescue operations, and to ask how powerful precedent can be in determining hostile encounters in international law.--
Caroline Incident, 1837 / Michael Wood -- Korean War, 1950-1953 / Nigel White -- Suez Canal Crisis, 1956 / Alexandra Hofer -- Soviet Intervention in Hungary, 1956 / Eliav Lieblich -- U-2 incident, 1960 / Ki-Gab Park -- Belgian Intervention in The Congo, 1960 and 1964 / Robert Kolb -- Indian Intervention in Goa / 1961 / Tom Ruys -- Cuban Missile Crisis, 1962 / Alexander Orakhelashvili -- Gulf of Tonkin Incident, 1964 / Douglas Guilfoyle -- US Intervention in the Dominican Republic, 1965 / Christian Walter -- Six Day War, 1967 / John Quigley -- Intervention in Czechoslovakia, 1968 / Gerhard Hafner -- USS Pueblo Incident, 1968 / Wolff Heintschel von Heinegg -- Indian Intervention into (East) Pakistan, 1971 / Dino Kristiotis -- Yom Kippur War, 1973 / Francois Dubuisson and Vaios Koutroulis -- Turkey's intervention in Cyprus, 1974 / Oliver Dorr -- Mayaguez Incident, 1975 / Natalino Ronzitti -- Entebbe Rai, 1976 / Claus Kress and Benjamin K. Nussberger -- Larnaca Incident, 1978 / Constantine Antonopoulos -- Vietnamese Intervention in Cambodia 1978 / Gregory H. Fox -- Ugandan-Tanzanian War, 1978-1979 / Kenneth Chan -- Operation Litani / 1978, Myra Williamson -- Lebanon War, 1982 / Myra Williamson -- Soviet Intervention in Afghanistan, 1979-1980 / Georg Nolte and Janina Barkholdt -- US Hostage Rescue Operation in Iran, 1980 / Mathias Forteau and Alison See Ying Xiu -- Iran-Iraq War, 1980-1988 / Andrea de Guttry -- Israel's Air Strike Against Iraq's Osiraq Nuclear Reactor, 1981 / Tom Ruys -- US Intervention in Nicaragua, 1981-1988 / Jorg Kammerhofer -- Falklands/Malvinas War, 1982 / Etienne Henry -- South African Incursions into Lesotho, 1982 / Theresa Reinold -- US Intervention in Grenada, 1983 / Nabil Hajjami -- Israeli Raid Against the PLO Headquarters in Tunis, 1985 / Erin Pobjie, Fanny Declercq, and Raphael Van Steenberghe -- Killing of Khalil al-Wazir by Israeli Commandos in Tunis, 1988 / Erin Pobjie, Fanny Declercq, and Raphael Van Steenberghe -- US Strikes Against Libya, 1986 / Maurice Kamto -- US Intervention in Panama, 1989 / Nicholas Tsagourias -- ECOWAS Intervention in Liberia, 1990-1997 / Ugo Villani -- Gulf War, 1990-1991 / Erika de Wet -- Intervention in Iraq's Kurdish region and the Creation of the No-Fly Zones in Northern and Southern Iraq, 1991-2003 / Tarcisio Gazzini -- Intervention in Somalia / Terry D. Gill and Kinga Tibori-Szabo -- Intervention in Bosnia and Herzegovina, 1992-1995 / Pierre Klein -- US Air Strike Against the Iraqi Intelligence Headquarters, 1993 / Paulina Starski -- ECOWAS Intervention in Sierra Leone, 1997-1999 / Susan Breau -- US Strikes in Sudan and Afghanistan, 1998 / Enzo Cannizzaro and Aurora Rasi -- Eritrean-Ethiopian War, 1998-2000 / Sean D. Murphy -- Great African War and the Intervention by Uganda and Rwanda in the Democratic Republic of Congo, 1998-2003 / James A. Green -- Kosovo crisis, 1999 / Daniel Franchini and Antonios Tzanakopoulos -- Intervention in Afghanistan, 2001- / Michael Byers -- Iraq War, 2003 / Marc Weller -- Israeli Air Strikes in Syria, 2003 and 2007 / Lindsay Moir -- Israeli Intervention in Lebanon, 2006 / Christian J. Tams and Wenke Bruckner -- Turkish Intervention Against the PKK in Northern Iraq, 2007-2008 / Kimberley N. Trapp -- Operation Phoenix, the Colombian Raid Against the FARC in Ecuador, 2008 / Monica Pinto and Marcos Kotlik -- Conflict in Georgia, 2008 / Christine Gray -- Israeli Military Operations Against Gaza : Operation Cast Lead (2008-2009), Operation Pillar of Defense (2012), and Operation Protective Edge (2014) / Christian Henderson -- NATO Intervention in Libya, 2011 / Ashley Deeks -- US Extra-Territorial Actions against Individuals : Bin Laden, Al Awlaki, and Abu Khattalah / David Kretzmer -- Intervention in Cote d'Ivoire, 2011 / Dire Tladi -- Intervention of the Gulf Cooperation Council in Bahrain, 2011 / Agatha Verdebout -- Ethiopian Military Intervention in Somalia, 2011 / Jean-Christophe Martin -- Intervention of France and African Countries in Mali 2013 / Karine Bannelier and Theodore Christakis -- Threats of and Actual Military Strikes against Syria, 2013 and 2017 / Anne Lagerwall -- Crisis in Ukraine, 2014 / Mary Ellen O'Connell -- Military Operations against the Islamic State (ISIL or Da'esh), 2014 / Olivier Corten -- Saudi-Led Military Intervention in Yemen's Civil War, 2015 / Luca Ferro and Tom Ruys -- ECOWAS Intervention in the Gambia, 2016 / Mohamed S. Helal.
Includes bibliographical references and index.
Keywords: United Nations; United Nations; Intervention (International law) -- Case studies; Aggression (International law) -- Case studies; Self-defense (International law) -- Case studies; War (International law) -- Case studies; 86.92 law of war; Peacekeeping forces; Treaties; Case studies; Case studies